Do UV-A radiation and blue light during growth prime leaves to cope with acute high light in photoreceptor mutants of Arabidopsis thaliana? - Brelsford, Craig C; Morales, Luis O; Nezval, Jakub; Kotilainen, Titta K; Hartikainen, Saara M; Aphalo, Pedro J; Robson, T Matthew (Physiologia plantarum, 2019)
We studied how plants acclimated to growing conditions that included combinations of blue light (BL) and ultraviolet (UV)-A radiation, and whether their growing environment affected their photosynthetic capacity during and after a brief period of acute high light (as might happen during an under-canopy sunfleck). Arabidopsis thaliana Landsberg erecta wild-type were compared with mutants lacking functional blue light and UV photoreceptors: phototropin 1, cryptochromes (CRY1 and CRY2) and UV RESISTANT LOCUS 8 (uvr8). This was achieved using light-emitting-diode (LED) lamps in a controlled environment to create treatments with or without BL, in a split-plot design with or without UV-A radiation. We compared the accumulation of phenolic compounds under growth conditions and after exposure to 30 min of high light at the end of the experiment (46 days), and likewise measured the operational efficiency of photosystem II (ϕPSII, a proxy for photosynthetic performance) and dark-adapted maximum quantum yield (Fv /Fm to assess PSII damage). Our results indicate that cryptochromes are the main photoreceptors regulating phenolic compound accumulation in response to BL and UV-A radiation, and a lack of functional cryptochromes impairs photosynthetic performance under high light. Our findings also reveal a role for UVR8 in accumulating flavonoids in response to a low UV-A dose. Interestingly, phototropin 1 partially mediated constitutive accumulation of phenolic compounds in the absence of BL. Low-irradiance BL and UV-A did not improve ϕPSII and Fv /Fm upon our acute high-light treatment; however, CRYs played an important role in ameliorating high-light stress.
Keywords: Photosystem II Protein Complex; Plant Leaves; Ultraviolet Rays; světlo; mutace; Arabidopsis Proteins; Mutation; ultrafialové záření; fotosystém II (proteinový komplex); Light; listy rostlin; Arabidopsis; proteiny huseníčku